2010
DOI: 10.1002/qua.22927
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of microscopic protonation constants of polybasic molecules via computational methods: A complete microequilibrium analysis of spermine

Abstract: For the first time, a simple methodology is reported for theoretical calculation of microscopic protonation constants of polybasic molecules in solution. Density functional theory study was used for complete microequilibrium analysis of spermine, H 2 N(CH 2 ) 3 NH(CH 2 ) 4 NH(CH 2 ) 3 NH 2 , a linear tetraamine with 16 known microspecies. A general thermodynamic cycle is proposed to calculate protonation microconstants of polybasic molecules using calculated micro-DG values in aqueous solution. The microscopic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 34 publications
1
11
0
Order By: Relevance
“…it is less stable) than the one selected from the Epath. A similar discrepancy between Gibbs free energy and electronic energy based selection of LECs has been reported by Salehzadeh et al [16] in their study of micro protonation constants of spermine.…”
Section: ) Hsupporting
confidence: 79%
See 3 more Smart Citations
“…it is less stable) than the one selected from the Epath. A similar discrepancy between Gibbs free energy and electronic energy based selection of LECs has been reported by Salehzadeh et al [16] in their study of micro protonation constants of spermine.…”
Section: ) Hsupporting
confidence: 79%
“…Many papers have focused on theoretical prediction of protonation constants for diverse biologically important compounds such as amines, amides, carboxylic acids, bicarbonates and proteins, amongst others [11,[16][17][18][19][20][21][22][23][24][25][26][27][28][29][30][31][32][33][34].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…In our previous works we have been successful in calculating the macroscopic and even microscopic protonation constants of polybasic molecules. 18 We have also been successful in predicting the formation constants of metal complexes of a series of tripodal tetraamines 19,20 and/or macrocyclic ligands 21 by studying their proton affinities. However, unfortunately, the results of our present calculations using different solvation models at different levels of theory (see Table S1) showed that the calculation of formation constants of present complexes is not simply possible.…”
Section: Comparison Of Anion Receptors In Solutionmentioning
confidence: 99%